Energetically-favorable distribution of oxygen vacancies and metal atoms in perovskite BaCexZr0.85−xY0.15O2.925 solid solutions using a genetic algorithm and lattice statics - Choi, In-Gyu; Kim, Yurie; Kim, Ki-Yung; Jo, Junyeong; Song, Sun-Ju; Kim, Yeong-Cheol (Computational materials science, 2019)
[Display omitted] We studied the energetically-favorable distribution of oxygen vacancies and metal atoms in perovskite BaCexZr1−xY0.15O2.925 solid solution structures using a genetic algorithm and lattice statics. The solid solution structures were made by mixing Ce, Zr, and Y at site B and removing O at site O in ABO3. Because of the huge number of configurational solid solution structures in the 3 × 3 × 3 ABO3 supercell, we employed a genetic algorithm and lattice statics to help identify energetically-favorable solid solution structures. Oxygen vacancies in the solid solution structures preferred Zr when the Ce composition was small, and the preference changed to Y with an increase in the Ce composition.